1998
DOI: 10.1002/(sici)1097-4636(19980915)41:4<593::aid-jbm11>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion ofPseudomonas aeruginosa to collagen biomaterials: Effect of amikacin and ciprofloxacin on the colonization and survival of the adherent organisms

Abstract: The adherence of P. aeruginosa to collagen membrane, sponge, and to a new anti-infective COLL dressing and the susceptibility of the organisms attached to the biomaterials to amikacin were investigated in vitro. After 17 h of attachment, the bacteria demonstrated an increased resistance to amikacin compared with their free-floating counterparts. Amikacin, even at a concentration exceeding 150 times the minimal bactericidal concentration (MBC) for the strain tested, did not eradicate the attached bacteria from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The SEM observation shows that the pore size of the sponge varies from 500 to 800 μm, because of the swelling nature of the material in aqueous medium, which allowed the drug to enter into the sponges and to bind on drying. Another superiority of the bilayer system over the other system is evident from the water‐vapor transmission study, a value of 1570 ± 25 g/m 2 /day1, which is more than the water‐vapor transmission rate of the commercially available dressings currently employed, for example, Comfeel (Coloplast A/s), Dermiflex (Johnson & Johnson), Duroderm (Conva Tec Ltd.), Metoderm (Conva Tec Ltd.), where the water‐vapor transmission rate ranges from 823 to 308 g/m 2 /day 29. Water‐uptake studies in the dressing show a high swelling rate at physiological pH, which confirms the high efficiency of dressing to absorb wound exudates.…”
Section: Discussionmentioning
confidence: 99%
“…The SEM observation shows that the pore size of the sponge varies from 500 to 800 μm, because of the swelling nature of the material in aqueous medium, which allowed the drug to enter into the sponges and to bind on drying. Another superiority of the bilayer system over the other system is evident from the water‐vapor transmission study, a value of 1570 ± 25 g/m 2 /day1, which is more than the water‐vapor transmission rate of the commercially available dressings currently employed, for example, Comfeel (Coloplast A/s), Dermiflex (Johnson & Johnson), Duroderm (Conva Tec Ltd.), Metoderm (Conva Tec Ltd.), where the water‐vapor transmission rate ranges from 823 to 308 g/m 2 /day 29. Water‐uptake studies in the dressing show a high swelling rate at physiological pH, which confirms the high efficiency of dressing to absorb wound exudates.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that E. faecalis that adhered to collagen was more resistant against IKI and CHX at different periods. One study that has investigated the effect of adhesion by Pseudomonas aeruginosa to collagen membrane also found significant resistance of the adhering bacteria against an aminoglycoside (22). However, the authors believed that this effect was the result of biofilm formation on the collagen membrane surface, a well‐recognized mechanism of antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, a number of polymeric materials have been studied as promising drug delivery system to provide improved delivery efficiency and to reduce side effects of drug toxicity 1. Collagen based biomaterials are considered as most promising substances for wound healing and skin regeneration 2. Successful wound graft out come requires adherence to wounds, histocompatibility, control of fluids loss and infection, absence of antigenecity and toxicity, mechanical stability and compliance, cost effectiveness, and ease of availability 3, 4.…”
Section: Introductionmentioning
confidence: 99%
“…Several antibiotics have been investigated as agents for the reduction of wound contaminations and to improve wound healing. But, amikacin and gentamycin have been implanted into the scaffolds without loss of its activity 2, 14. Moreover, these antibiotics are active against both gram‐positive and gram‐negative bacteria.…”
Section: Introductionmentioning
confidence: 99%